Understanding Kampung Transformation through Development Thinking Perspective: Insights from ‘Kampung Berkebun Pajajaran’ - Dzaki, Hilmy Muhammad; Mulyati, Sri; Arkan, Muhammad Wildan; Yuliar, Sonny (Universitas Diponegoro Publishing Group, Indonesia, 2025)
Learning about slum upgrading, with a particular focus on activity transformation, is critical for addressing slum problems resulting from rapid urbanization. Consequently, this research focuses on ‘Kampung Berkebun Pajajaran’, Bandung, as a case study of a successful slum transformation. Previous research has focused partially on specific aspects of transformation. This article employs the development thinking framework to analyze the complete picture, examining the interplay between the program, community's agency, initiatives, and external support structures. This framework equips researchers with a critical lens to provide a comprehensive analysis of the dynamics of activity transformation that occurred. The findings indicate that development thinking framework offers a more comprehensive understanding of the transformation from a broader perspective. The results demonstrate that the community prioritized values of solidarity, self-reliance, and collaboration to achieve progress. Their vision of reduced dependency materialized through the urban farming initiative, generating social, economic, and environmental benefits.